Early neonatal dermatoses: An epidemiological study from a tertiary care center in Western Rajasthan - Paras Choudhary; Rajesh D Mehta; Kamaldeep Singh; Vikas Mahla; Bhikam C Ghiya; Divya Sharma; Ashok Dhanwal (Wolters Kluwer Medknow Publications, 2023)
Background: The spectrum of cutaneous manifestations during the neonatal period varies from transient self-limiting conditions to serious life-threatening ones. Transient and pathological neonatal dermatoses should be differentiated from physiological changes to avoid unnecessary treatment and to relieve parent's stress. Purpose: The aim of this study was to determine the incidence and patterns of various dermatoses in early neonates and correlate these changes with maternal or neonatal factors; in the west region of Rajasthan, India. Methods: This hospital-based prospective study at a tertiary-level referral teaching medical center entailed recording detailed dermatological examination of 5000 early neonates having any physiological and/or pathological cutaneous changes. Results: A total of 5000 newborns were observed, there were 3248 (64.96%) male and 1752 (35.04%) female. Out of the total, 67.36% were full-term birth, whereas 30.44% were preterm and 2.2% were postterm newborns. Physiological skin changes (92.42%) were more commonly observed as compared to pathological changes (45.1%). The physiological skin changes observed in the order of frequency were sebaceous hyperplasia (65.32%), milia (51.12%), and physiological scaling (41.02%). Cutis marmorata (2.06%) and harlequin skin changes (1.06%) were seen more in preterms, weighing <2.5 kg. Miliaria was observed in 39% of neonates, due to the hot and humid environment at our place. Bullous impetigo was the most common infection observed in 199 neonates. The most common iatrogenic complication was caput succedaneum; noted in 160 neonates. Conclusion: Neonatal dermatoses are mostly transient and physiological, but these innocent dermatoses need to be differentiated from serious and aggressive pathological dermatoses to avoid unnecessary therapy.